2017
DOI: 10.1002/jcp.26128
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ZL55 cell proliferation by ADP via PKC‐dependent signalling pathway

Abstract: Extracellular nucleotides can regulate cell proliferation in both normal and tumorigenic tissues. Here, we studied how extracellular nucleotides regulate the proliferation of ZL55 cells, a mesothelioma-derived cell line obtained from bioptic samples of asbestos-exposed patients. ADP and 2-MeS-ADP inhibited ZL55 cell proliferation, whereas ATP, UTP, and UDP were inactive. The nucleotide potency profile and the blockade of the ADP-mediated inhibitory effect by the phospholipase C inhibitor U-73122 suggest that P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…We demonstrated previously that ADP induces a dose‐ and time‐dependent activation of ERK1/2 in ZL55 cells …”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…We demonstrated previously that ADP induces a dose‐ and time‐dependent activation of ERK1/2 in ZL55 cells …”
Section: Resultsmentioning
confidence: 83%
“…Our results demonstrate for the first time that the P2Y1 receptor, following ADP (or 2‐MeS‐ADP) stimulation, increases the expression of MMP2/9 and induces their nuclear localization in human epithelioid ZL55 mesothelioma cells. Previously, we showed the expression in ZL55 cells of the P2Y1, P2Y4, P2Y6, and P2Y11 subtypes of nucleotide receptors, and that the inhibition of ZL55 cell proliferation occurred through activation of P2Y1 receptors …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…37,38 Different signal transduction pathways transduce the control of inflammation by P2Y receptors, including the mitogen-activated protein kinases, ERK1/2, p38, and JNK. 11 P2Y activation has been showed to induce the downstream increase in phosphorylation of ERK and induce the release of proinflammatory cytokines such as IL-6, IL-8, MCP-1, IL-1β. 39,40 In our study, we found that ADP at high concentrations significantly induced the mRNA expression of VCAM-1 and ICAM-1, and induced a time-dependent increase in ERK1/2 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%